2021
DOI: 10.1038/s41598-021-85271-w
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to ripasudil may be a potential outcome marker for selective laser trabeculoplasty in patients with primary open-angle glaucoma

Abstract: We examined responsiveness to ripasudil as a potential factor for predicting the effect of selective laser trabeculoplasty (SLT) when performed for primary open-angle glaucoma (POAG). A total of 70 eyes with no history of glaucoma surgery underwent SLT between January 2015 and June 2019. Patients were divided into two groups, with an intraocular pressure (IOP) decrease of 15% or more due to ripasudil administration before SLT defined as the effective group, while an IOP decrease of less than 15% was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It has a different mode of action compared to traditional medication in a way that it causes TM and Schlemm's canal changes, resulting in a higher uveoscleral outflow, lowering IOP [114]. It was shown that patients who respond well to treatment with ripasudil had significantly better SLT success ratios compared to patients who were unresponsive to ripasudil treatment [115].…”
Section: Other Considerations: Retreatment Predictors Of Success Cost...mentioning
confidence: 99%
“…It has a different mode of action compared to traditional medication in a way that it causes TM and Schlemm's canal changes, resulting in a higher uveoscleral outflow, lowering IOP [114]. It was shown that patients who respond well to treatment with ripasudil had significantly better SLT success ratios compared to patients who were unresponsive to ripasudil treatment [115].…”
Section: Other Considerations: Retreatment Predictors Of Success Cost...mentioning
confidence: 99%
“…Previous studies reported the relationship, comparisons, and treatment effects of ripasudil and SLT. Baba et al reported increased success rates of SLT in patients with ripasudil-effective glaucoma [ 23 ]. Ono et al reported that both adjuvant ripasudil and SLT reduced IOP significantly in patients with inadequately controlled glaucoma, and the percentage reduction in IOP between the two groups was not statistically significant [ 24 ].…”
Section: Discussionmentioning
confidence: 99%